The Wiener Index for Neutrosophic Labeling Graphs and Its Application in River Ecosystem Analysis - Gomathi, M.; Prema, S.; Preethi, N. (Communications in Mathematics and Applications, 2025)
This paper explores several topological indices in neutrosophic labeling graphs, including Randic’s, Zagreb, connectivity, and harmonic indices. Theorems linked to concepts are proved using appropriate instances. Application of the Wiener index is analyzed in river basin ecosystems across different seasons to understand seasonal changes in the ecosystem’s structure and interactions. This approach gives detailed information about the uncertainties and natural variations in river systems.
Keywords: Neutrosophic labeling graphs; Randic index; Zagreb indices; Connectivity index; Harmonic index; Neutrosophic labeling Weiner index